Modified lithium iron phosphate as well as preparation method and application thereof

The particle size distribution of lithium iron phosphate is optimized through dry or wet grinding technology, which solves the problem of uneven particle distribution, improves the circulation performance and grams capacity of lithium-ion batteries, and optimizes the processing performance.

CN119725520APending Publication Date: 2025-03-28XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411949526.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The particle distribution of the positive electrode sheet of lithium iron phosphate battery is uneven, which affects the circulation performance and capacity, and too many small particles lead to a decrease in processing performance.

Method used

Through dry or wet grinding technology, the particle size distribution of lithium iron phosphate is optimized, large particles dispersion and small particles agglomeration are promoted, and the circulation performance and gram capacity of the battery are improved.

Benefits of technology

The circulation performance and gram capacity of lithium-ion batteries are improved, the processing performance is optimized, the proportion of extremely small particles is reduced, and the dispersion performance and discharge solid content are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725520A_ABST
    Figure CN119725520A_ABST
Patent Text Reader

Abstract

The invention discloses modified lithium iron phosphate as well as a preparation method and application thereof, and the preparation method of the modified lithium iron phosphate comprises the following step: carrying out dry grinding or / and wet grinding on lithium iron phosphate to obtain the modified lithium iron phosphate. According to the preparation method of the modified lithium iron phosphate, in the dry grinding or / and wet grinding process of the commercial lithium iron phosphate, large particles formed by agglomeration can be separated, and small-particle powder can be slightly agglomerated, so that the particle size distribution of the powder is optimized, and the cycle performance of a lithium ion battery applying the modified lithium iron phosphate prepared from the powder is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a modified lithium iron phosphate and a preparation method and application thereof. Background Art

[0002] At present, with the increasing requirements for the capacity of lithium-ion batteries, the compaction density of the battery cell pole piece is also increasing. In order to improve the compaction density of the positive pole piece of lithium iron phosphate batteries, the powder compaction of lithium iron phosphate is one of the most critical indicators. Currently, one of the most common ways to improve powder compaction is to use large and small particle grading technology, using small particles to fill the gaps between large particles, thereby increasing the powder compaction of lithium iron phosphate.

[0003] However, the uneven distribution of lithium iron phosphate particles has an adverse effect on the cycle performance and capacity of the battery. Large particles produce polarization, while small particles have a high specific surface area, high reaction activity, and a relatively high degree of side reactions.

[0004] Disadvantages of existing technology:

[0005] 1. The uneven distribution of lithium iron phosphate particles using grading technology has an adverse effect on the cycle performance and capacity of the battery. Large particles produce polarization, small particles have a high specific surface area, high reaction activity, and a relatively high degree of side reactions.

[0006] 2. There are many small particles, which also affect the processing performance. The increase in specific surface area will lead to a decrease in solid content, an increase in viscosity, and is not conducive to dispersion. Summary of the invention

[0007] In view of this, an object of the present application is to provide a method for preparing modified lithium iron phosphate. During the process of dry grinding and / or wet grinding of commercial lithium iron phosphate, the large particles formed by agglomeration will be separated, and the small particle powder will be slightly agglomerated, thereby optimizing the particle size distribution of the powder, thereby improving the cycle performance of the lithium-ion battery using the modified lithium iron phosphate prepared thereby.

[0008] Another object of the present application is to provide a modified lithium iron phosphate.

[0009] Another object of the present application is to provide a positive electrode plate.

[0010] Another object of the present application is to provide a secondary battery.

[0011] To achieve the above objectives, the first aspect of the present application proposes a method for preparing modified lithium iron phosphate, comprising:

[0012] The lithium iron phosphate is subjected to dry grinding or / and wet grinding to obtain the modified lithium iron phosphate.

[0013] In some embodiments, the lithium iron phosphate is lithium iron phosphate prepared using a large and small particle grading technology.

[0014] In some embodiments, the dry grinding comprises dry ball milling.

[0015] In some embodiments, the wet grinding comprises wet ball milling.

[0016] In some embodiments, the solvent for wet grinding includes at least one of water, acetone, and xylene.

[0017] In some embodiments, during the wet grinding process, the mass ratio of the lithium iron phosphate to the solvent is 1:(5-15).

[0018] In some embodiments, the grinding temperature of the dry grinding and / or wet grinding is room temperature.

[0019] In some embodiments, the grinding time of the dry grinding and / or wet grinding is 60-120 min.

[0020] In some embodiments, the grinding speed of the dry grinding and / or wet grinding is 100-500 rpm.

[0021] In some embodiments, during the dry grinding or / and wet grinding process, zirconium balls with a diameter of 4-6 mm are used, and the mass ratio of the lithium iron phosphate to the zirconium balls is 1:(8-12).

[0022] In some embodiments, the method for preparing modified lithium iron phosphate further comprises a drying step after the dry grinding and / or wet grinding.

[0023] In some embodiments, the drying is performed under vacuum conditions.

[0024] In some embodiments, the drying temperature is 70-90°C.

[0025] In some embodiments, the drying time is 20-28 hours.

[0026] A second aspect of the present application provides a modified lithium iron phosphate, which is prepared using the preparation method of the modified lithium iron phosphate described in the present application.

[0027] In some embodiments, the minimum value of the modified lithium iron phosphate D01 is 0.10 μm.

[0028] In some embodiments, the maximum value of the modified lithium iron phosphate D99 is 25.0 μm.

[0029] In some embodiments, the particle size of the modified lithium iron phosphate ranges from 0.10 μm to 25.0 μm.

[0030] In some embodiments, the D50 of the modified lithium iron phosphate is 0.70-1.50 μm.

[0031] In some embodiments, the D90 of the modified lithium iron phosphate is 3.50-8.50 μm.

[0032] In some embodiments, the compacted density of the modified lithium iron phosphate is 2.35-2.55 g / cm 3 .

[0033] A third aspect of the present application provides a positive electrode plate, comprising a positive electrode active material, wherein the positive electrode active material comprises the modified lithium iron phosphate described in the present application.

[0034] A fourth aspect of the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate and a separator, wherein the positive electrode plate is the positive electrode plate described in the present application.

[0035] The preparation method of modified lithium iron phosphate described in this application can at least bring the following beneficial effects:

[0036] 1. Improve cycle performance: Dry grinding or / and wet grinding of commercial lithium iron phosphate optimizes the particle size distribution of lithium iron phosphate, promotes the agglomeration of small particles, and the dispersion of agglomerated large particles, thereby improving the cycle performance of lithium-ion batteries.

[0037] 2. Increased gram capacity: Large particles formed by agglomeration will separate, which can promote the transmission of lithium ions and increase the gram capacity of the battery cell.

[0038] 3. When wet grinding, especially wet ball milling, can be used as a medium with a smaller polarity such as water. Solvents with different polarities have different dispersion effects on particles, and optimize the particle size distribution of the powder to varying degrees. Specifically, solvents with smaller polarity have a higher and better dispersion effect on lithium iron phosphate, which is more conducive to zirconium beads separating large particles of secondary agglomeration. The modified lithium iron phosphate has a higher gram capacity and better cycle performance.

[0039] 4. Optimized processing performance: By reducing the proportion of extremely small particles, the dispersion performance is improved, the solid content of the discharge is increased, and the discharge viscosity is reduced.

[0040] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.

[0042] in:

[0043] Figure 1 It is a comparison chart of the particle size distribution of the blank group (comparative example) and the modified lithium iron phosphate / lithium iron phosphate of Examples 1-3.

[0044] Figure 2 It is a comparison chart of the particle size distribution of the blank group (comparative example) and the modified lithium iron phosphate / lithium iron phosphate of Examples 4-6.

[0045] Figure 3 It is a comparison chart of the particle size distribution of the blank group (comparative example) and the modified lithium iron phosphate / lithium iron phosphate of Examples 7-9. DETAILED DESCRIPTION

[0046] The embodiments of the present application are described in detail below. The embodiments are exemplary and intended to be used to explain the present application, but should not be construed as limiting the present application.

[0047] In this application, the disclosure of numerical ranges includes all values ​​within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.

[0048] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.

[0049] The term "and / or", when used in a list of two or more items, means that any of the listed items can be used alone or in combination with any one or more of the listed items. For example, the expression "A and / or B" is intended to mean A or B or A and B, that is, only A, only B, or a combination of A and B.

[0050] In this application, room temperature refers to 20-30°C.

[0051] the term:

[0052] D01 refers to the particle size corresponding to when the cumulative distribution in the material reaches 1%.

[0053] D10 refers to the particle size corresponding to when the cumulative distribution in the material reaches 10%.

[0054] D50 refers to the particle size corresponding to when the cumulative distribution in the material reaches 50%, which is also generally called the median particle size.

[0055] D90 refers to the particle size corresponding to when the cumulative distribution in the material reaches 90%.

[0056] D99 refers to the particle size corresponding to when the cumulative distribution in the material reaches 99%.

[0057] For example, if D10=0.5μm, D50=1μm, D90=8μm, and D99=25μm of a certain material are distributed from small to large particles, it means that among all the particle systems that make up the material, particles less than or equal to 0.5μm account for 10%; particles less than or equal to 1μm account for 50%; particles less than or equal to 8μm account for 90%; and particles less than or equal to 25μm account for 99%.

[0058] In a first aspect, a method for preparing modified lithium iron phosphate according to an embodiment of the present application comprises: dry grinding or / and wet grinding the lithium iron phosphate to obtain the modified lithium iron phosphate.

[0059] In the embodiments of the present application, the lithium iron phosphate to be dry ground or / and wet ground is a lithium iron phosphate product produced by using large and small particle grading technology (two or more peaks appear in a secondary particle size analyzer).

[0060] It is understood that in the process of modifying lithium iron phosphate, the preparation method of the modified lithium iron phosphate in the embodiment of the present application can only use dry grinding, only use wet grinding, or combine dry grinding and wet grinding. Further, the grinding method is not limited, and can be manual grinding, mechanical grinding, etc.

[0061] In some embodiments, the dry grinding comprises dry ball milling.

[0062] In other embodiments, the wet grinding comprises wet ball milling.

[0063] In the embodiments of the present application, when wet grinding is used, the solvent is selected to have a relatively low polarity. In the ball milling modification, the relatively low polarity solvent has a higher and better dispersion of lithium iron phosphate, and is more conducive to the zirconium beads separating the large particles of secondary agglomeration, and the modified lithium iron phosphate has a higher gram capacity and better cycle performance.

[0064] In some embodiments, the solvent for wet grinding includes but is not limited to at least one of water, acetone, xylene, etc. Among them, the polarity of water is greater than that of acetone, and the polarity of acetone is greater than that of xylene.

[0065] In some embodiments, during the wet grinding process, the mass ratio of the lithium iron phosphate to the solvent is 1:(5-15), including but not limited to 1:5.5, 1:7.5, 1:10, 1:12.5 or 1:14.

[0066] In the embodiments of the present application, the mass ratio of lithium iron phosphate to solvent in wet grinding is within the above range, the shear stress between powders and between zirconium beads and powders is in a relatively balanced state, and at the same time, the temperature of the ball milling will not be too high, the large particles of secondary adhesion will be separated, the original primary particles of the powder will not be destroyed, and the smaller primary particles or secondary particles will be slightly agglomerated; if it is lower than 1:5, the temperature of the material will rise too quickly during ball milling, and the powder will be unevenly dispersed in the solvent, affecting the ball milling effect; if it is higher than 1:15, the resistance will increase during ball milling, the collision frequency between powders and between powders and zirconium beads will be less, and the dispersion will be insufficient.

[0067] As an optional example, during the wet grinding process, the mass ratio of the lithium iron phosphate to the solvent is 1:10.

[0068] In some embodiments, the grinding temperature of the dry grinding and / or wet grinding is room temperature.

[0069] In some embodiments, the grinding time of the dry grinding and / or wet grinding is 60-120 min, including but not limited to 70 min, 80 min, 90 min, 100 min or 110 min, etc.

[0070] As an optional example, the grinding time of the dry grinding and / or wet grinding is 90 minutes.

[0071] In some embodiments, the grinding speed of the dry grinding and / or wet grinding is 100-500 rpm, including but not limited to 120 rpm, 210 rpm, 300 rpm, 390 rpm or 480 rpm, etc.

[0072] In some embodiments, during the dry grinding or / and wet grinding process, zirconium balls with a diameter of 4-6 mm are used, and the mass ratio of the lithium iron phosphate to the zirconium balls is 1:(8-12).

[0073] Exemplarily, the diameter of the zirconium ball includes but is not limited to 4.5 mm, 5 mm or 5.5 mm.

[0074] Exemplarily, the mass ratio of the lithium iron phosphate to the zirconium ball includes, but is not limited to, 1:9, 1:10 or 1:11, etc., and can be optionally 1:10.

[0075] In some embodiments, the method for preparing modified lithium iron phosphate further comprises a drying step after the dry grinding and / or wet grinding.

[0076] In some embodiments, the drying is performed under vacuum conditions.

[0077] Exemplarily, the vacuum degree during the drying process is 0.05-0.15 MPa, including but not limited to 0.07 MPa, 0.1 MPa, or 0.13 MPa, etc., and can be optionally 0.1 MPa.

[0078] In some embodiments, the drying temperature is 70-90°C, including but not limited to 75°C, 80°C or 85°C.

[0079] In some embodiments, the drying time is 20-28 hours, including but not limited to 21 hours, 23 hours, 25 hours or 27 hours.

[0080] As an optional example, the drying time is 24 hours.

[0081] The preparation method of modified lithium iron phosphate described in this application can at least bring the following beneficial effects:

[0082] 1. Improve cycle performance: Dry grinding or / and wet grinding of commercial lithium iron phosphate optimizes the particle size distribution of lithium iron phosphate, promotes the agglomeration of small particles, and the dispersion of agglomerated large particles, thereby improving the cycle performance of lithium-ion batteries.

[0083] 2. Increased gram capacity: Large particles formed by agglomeration will separate, which can promote the transmission of lithium ions and increase the gram capacity of the battery cell.

[0084] 3. When wet grinding, especially wet ball milling, solvents of different polarities such as water can be used as the medium. Solvents of different polarities have different dispersion effects on particles, and optimize the particle size distribution of the powder to varying degrees. Specifically, solvents with lower polarity have a higher and better dispersion effect on lithium iron phosphate, which is more conducive to zirconium beads separating large particles of secondary agglomeration. The modified lithium iron phosphate has a higher gram capacity and better cycle performance.

[0085] 4. Optimized processing performance: By reducing the proportion of extremely small particles, the dispersion performance is improved, the solid content of the discharge is increased, and the discharge viscosity is reduced.

[0086] In a second aspect, the modified lithium iron phosphate of the embodiment of the present application is prepared by the preparation method of the modified lithium iron phosphate of the embodiment of the present application.

[0087] In some embodiments, the minimum value of the modified lithium iron phosphate D01 is 0.10 μm.

[0088] In some embodiments, the maximum value of the modified lithium iron phosphate D99 is 25.0 μm.

[0089] In some embodiments, the particle size of the modified lithium iron phosphate ranges from 0.10 μm to 25.0 μm.

[0090] It can be understood that in the embodiments of the present application, the particle size range of the modified lithium iron phosphate can be expressed by the above-mentioned minimum value of D01 and the maximum value of D99, that is, the particle size range of the modified lithium iron phosphate is between the minimum value of D01 and the maximum value of D99 and includes the minimum value of D01 and the maximum value of D99.

[0091] In some embodiments, the median particle size (D50) of the modified lithium iron phosphate is 0.70-1.50 μm, including but not limited to 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm or 1.3 μm, etc.

[0092] In some embodiments, the D90 of the modified lithium iron phosphate is 3.50-8.50 μm, including but not limited to 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm or 7 μm, etc.

[0093] In some embodiments, the compacted density of the modified lithium iron phosphate is 2.35-2.55 g / cm 3 , including but not limited to 2.4g / cm 3 , 2.45g / cm 3 or 2.5g / cm 3 wait.

[0094] In a third aspect, the positive electrode plate of the embodiment of the present application includes a positive electrode active material, and the positive electrode active material includes the modified lithium iron phosphate of the embodiment of the present application.

[0095] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer formed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode material, the positive electrode material includes a positive electrode active material, and the positive electrode active material includes the modified lithium iron phosphate of an embodiment of the present application.

[0096] In some embodiments, the positive electrode material may further include a positive electrode binder, a positive electrode conductor, and the like.

[0097] It should be noted that in the embodiments of the present application, there is no restriction on the specific selection of the positive electrode current collector, positive electrode binder, positive electrode conductive agent, etc. They can be any positive electrode current collector, positive electrode binder, positive electrode conductive agent, etc. that are well known in the art and can be used in secondary batteries, especially lithium-ion batteries.

[0098] In a fourth aspect, the secondary battery of the present application comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet of the embodiment of the present application.

[0099] In some embodiments, the secondary battery includes a lithium ion battery or the like.

[0100] It should be noted that in the embodiments of the present application, there is no limitation on the specific selection of the negative electrode plates and separators, etc. They can be any negative electrode plates and separators known in the art that can be used in secondary batteries, especially lithium-ion batteries.

[0101] Certain features of the present technology are further illustrated in the following non-limiting examples.

[0102] 1. Examples and Comparative Examples

[0103] The commercially available lithium iron phosphate involved in each embodiment is a lithium iron phosphate product that adopts the large and small particle grading technology (two or more peaks appear in the secondary particle size analyzer), and its physical and chemical performance indicators are shown in Table 1.

[0104] Table 1 Physical and chemical performance indicators of commercially available lithium iron phosphate involved in each embodiment

[0105]

[0106]

[0107] Example 1

[0108] The preparation method of the modified lithium iron phosphate of this embodiment comprises the following steps:

[0109] (1) Using a German Fitzpatrick ball mill, commercially available lithium iron phosphate was dry-milled at room temperature (25° C.) using zirconium balls with a diameter of 5 mm at a ball milling speed of 210 rpm for 90 min to obtain ball-milled lithium iron phosphate.

[0110] Among them, the mass ratio of lithium iron phosphate to zirconium balls is 1:10, and the volume of the grinding bowl is 500ml.

[0111] (2) The ball-milled lithium iron phosphate obtained in step (1) was dried at 80° C. for 24 h under vacuum conditions (vacuum degree of 0.1 MPa) to obtain the modified lithium iron phosphate of this embodiment.

[0112] Example 2

[0113] This embodiment is basically the same as Embodiment 1, except that:

[0114] Step (1) is: using a German Fitzpatrick ball mill, at room temperature (25° C.), commercially available lithium iron phosphate is wet-milled using zirconium balls with a diameter of 5 mm in a solvent xylene at a ball milling speed of 300 rpm for 90 minutes to obtain ball-milled lithium iron phosphate.

[0115] Among them, the mass ratio of lithium iron phosphate to zirconium balls is 1:10, the volume of the grinding bowl is 500 ml, and the mass ratio of lithium iron phosphate to solvent is 1:10.

[0116] Example 3

[0117] This embodiment is basically the same as Embodiment 2, except that:

[0118] In step (1), the solvent is acetone.

[0119] Example 4

[0120] This embodiment is basically the same as Embodiment 2, except that:

[0121] In step (1), the solvent is water.

[0122] Embodiment 5 (compared with embodiment 2, the solvent is a mixed solvent)

[0123] This embodiment is basically the same as Embodiment 2, except that:

[0124] In step (1), the solvent is a mixed solvent of xylene, acetone and water in a mass ratio of 1:1:1.

[0125] Example 6 (Compared with Example 2, the mass ratio of lithium iron phosphate to solvent is the lower limit)

[0126] This embodiment is basically the same as Embodiment 2, except that:

[0127] In step (1), the mass ratio of lithium iron phosphate to solvent is 1:5.

[0128] Example 7 (Compared with Example 2, the mass ratio of lithium iron phosphate to solvent is the upper limit)

[0129] This embodiment is basically the same as Embodiment 2, except that:

[0130] In step (1), the mass ratio of lithium iron phosphate to solvent is 1:15.

[0131] Example 8 (Compared with Example 2, the ball milling speed is close to the lower limit)

[0132] This embodiment is basically the same as Embodiment 2, except that:

[0133] In step (1), the wet milling was performed at a ball milling speed of 120 rpm for 90 min.

[0134] Example 9 (Compared with Example 2, the ball milling speed is close to the upper limit)

[0135] This embodiment is basically the same as Embodiment 2, except that:

[0136] In step (1), the wet milling was performed at a ball milling speed of 480 rpm for 90 min.

[0137] Comparative example (blank group)

[0138] The lithium iron phosphate used in this comparative example is the commercially available lithium iron phosphate used in Example 1 and Example 2, and is a lithium iron phosphate product produced by using large and small particle grading technology (two or more peaks appear in a secondary particle size analyzer).

[0139] The common preparation method of the commercially available lithium iron phosphate product is: after two precursor iron phosphates with different particle size distributions, one with larger average particle size and the other with smaller average particle size, are evenly mixed, and then put into a premixing device together with lithium carbonate and a carbon source, and then produced through a conventional lithium iron phosphate iron phosphate preparation process, and finally discharged. This is the conventional method for producing commercial lithium iron phosphate by the solid phase iron phosphate method on the market, which is not the invention content of this patent and will not be repeated here.

[0140] 2. Material Characterization and Performance Testing

[0141] 1. Particle size distribution

[0142] The particle size of the modified lithium iron phosphate / lithium iron phosphate prepared in each embodiment or comparative example was tested, and the specific test method was referred to the national standard GBT19077.1.

[0143] The test results are shown in Table 1 and Figure 1-3 shown.

[0144] from Figure 1-3 It can be seen that the lithium iron phosphate of the blank group (comparative example) has two peaks. The large and small particle grading technology was used in production, and the particle distribution is relatively wide. However, the modified lithium iron phosphate of Examples 1-9 has a more concentrated particle distribution due to ball milling. The main gain effect is that the size of large particles is reduced and the particle size of small particles is slightly increased.

[0145] 2. Compacted density

[0146] The compaction density of the modified lithium iron phosphate / lithium iron phosphate prepared in each embodiment or comparative example was tested, and the specific test method was referred to the national standard GB / T 24533.

[0147] The test results are shown in Table 2.

[0148] Table 2 Particle size and compacted density of modified lithium iron phosphate / lithium iron phosphate in each embodiment and comparative example

[0149]

[0150] As can be seen from Table 2, after ball milling modification, the large particle size has been significantly reduced, and the small particle size has increased slightly. Due to the natural defect of uneven mixing between the powder sample and the liquid sample, the particle size distribution only represents the sample taken, and cannot fully reflect the true particle size distribution of the entire powder, and is only representative. In this case, we can still see from the data of D90 and D99 that after ball milling, the large particle size of the powder of each embodiment becomes smaller. The compacted density is basically stable and unchanged.

[0151] 3. Performance testing

[0152] The modified lithium iron phosphate / lithium iron phosphate prepared in each example or comparative example was used as a positive electrode active material to prepare a lithium ion battery (3.2 Ah), and the performance of each lithium ion battery was tested.

[0153] Specific:

[0154] A method for preparing a lithium ion battery comprises the following steps:

[0155] 1) Preparation of positive electrode sheet: Take the modified lithium iron phosphate or lithium iron phosphate prepared in each embodiment or comparative example, conductive carbon black (SP), and binder polyvinylidene fluoride (PVDF) in a mass ratio of 97:1:2 and mix them evenly, add N-methylpyrrolidone, and further mix them evenly to obtain a positive electrode slurry; apply the positive electrode slurry (the current collector is an aluminum foil with a thickness of 14 μm, which is applied on the opposite sides of the current collector), dry it, roll it, cut it, and obtain a positive electrode sheet

[0156] 2) Preparation of negative electrode sheet: artificial graphite, conductive carbon black (SP), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are respectively mixed in a mass ratio of 96:1:1.3:1.7, deionized water is added, mixed evenly, and coated (the current collector is a copper foil with a thickness of 6 μm, which is coated on the opposite sides of the current collector), and then rolled and cut after drying to obtain the negative electrode sheet.

[0157] 3) Preparation of electrolyte: TC02 from Tianci Company.

[0158] 4) Selection of diaphragm: Enjie Company's 12μm isolation membrane.

[0159] 5) Assembly: The positive electrode sheet, negative electrode sheet and separator are stacked and the electrolyte is injected to make a lithium-ion battery soft pack; after the formation, aging, capacity division and other processes, the battery cell is offline.

[0160] The viscosity of the positive electrode slurry is tested by using a rotational viscometer in accordance with the national standard GB / T 22235.

[0161] The test method for gram capacity is: using a charge and discharge tester, the test steps are as follows:

[0162] 1. 0.1C constant current charging to 3.75V, voltage cut-off;

[0163] 2. 0.1C constant voltage charging, 0.05C rate cut-off;

[0164] 3. Leave for 30 minutes;

[0165] 4. 0.1C discharge, cut-off voltage 2.0V

[0166] The test method for cycle performance is: using a charge and discharge tester, the test steps are as follows:

[0167] 1. 0.1C constant current charging to 3.65V, voltage cut-off;

[0168] 2. 0.1C constant voltage charging, 0.05C rate cut-off;

[0169] 3. Leave for 30 minutes;

[0170] 4. 0.1C discharge, cut-off voltage 2.5V;

[0171] 5. Leave for 30 minutes;

[0172] 6. Repeat steps 1-5 600 times.

[0173] The performance test results are shown in Table 3.

[0174] Table 3 Performance test results

[0175]

[0176]

[0177] It can be seen from Table 3 that after 600 cycles, the capacity retention rate of the commercial lithium iron phosphate modified by ball milling with xylene as the solvent (Example 2) is about 1% higher than that before modification (blank group of the comparative example). The cycle performance of commercial lithium iron phosphate modified by ball milling with other solvents and dry milling is also improved to varying degrees.

[0178] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0179] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing modified lithium iron phosphate, characterized in that: include: The lithium iron phosphate is subjected to dry grinding or / and wet grinding to obtain the modified lithium iron phosphate.

2. The preparation method according to claim 1, characterized in that: The dry grinding comprises dry ball milling; and / or, The wet grinding comprises wet ball milling; and / or, The lithium iron phosphate is prepared by using large and small particle grading technology.

3. The preparation method according to claim 1, characterized in that: The solvent of the wet grinding includes at least one of water, acetone and xylene; and / or, During the wet grinding process, the mass ratio of the lithium iron phosphate to the solvent is 1:(5-15).

4. The preparation method according to claim 1, characterized in that: The grinding temperature of the dry grinding and / or wet grinding is room temperature; and / or, The dry grinding and / or wet grinding has a grinding time of 60-120 min; and / or, The grinding speed of the dry grinding and / or wet grinding is 100-500 rpm; and / or, During the dry grinding and / or wet grinding process, zirconium balls with a diameter of 4-6 mm are used, and the mass ratio of the lithium iron phosphate to the zirconium balls is 1:(8-12).

5. The preparation method according to any one of claims 1 to 4, characterized in that: The method for preparing modified lithium iron phosphate further comprises a drying step after the dry grinding and / or wet grinding.

6. The preparation method according to claim 5, characterized in that: The drying is carried out under vacuum conditions; and / or, The drying temperature is 70-90°C; and / or, The drying time is 20-28 hours.

7. A modified lithium iron phosphate, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. The modified lithium iron phosphate according to claim 7, characterized in that: The minimum value of the modified lithium iron phosphate D01 is 0.10 μm; and / or, The maximum value of the modified lithium iron phosphate D99 is 25.0 μm; and / or, The particle size of the modified lithium iron phosphate ranges from 0.10 μm to 25.0 μm; and / or, The D50 of the modified lithium iron phosphate is 0.70-1.50 μm; and / or, The D90 of the modified lithium iron phosphate is 3.50-8.50 μm; and / or, The compaction density of the modified lithium iron phosphate is 2.35-2.55 g / cm 3 .

9. A positive electrode sheet, comprising a positive electrode active material, characterized in that: The positive electrode active material includes the modified lithium iron phosphate as claimed in claim 7 or 8.

10. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The positive electrode sheet is the positive electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • A method for preparing high-capacity, high-density lithium iron phosphate material and its product

    CN102275887A

  • Preparation method of lithium iron phosphate

    CN103303893A

  • High-compaction low-temperature lithium iron phosphate material, lithium battery positive plate and preparation method thereof

    CN113086959A

  • Preparation method of high-energy-density lithium iron phosphate material

    CN115650200A

  • High-compaction lithium iron phosphate, preparation method thereof, positive plate and lithium ion battery

    CN116216679A